Defensive behavior of the invasive alien hornet Vespa velutina nigrithorax against potential human aggressors. Issue 4 (30th March 2021) - Choi, Moon Bo
Abstract: In areas where wasps are common, many wasp sting incidents occur. However, guidance on the correct response to wasp attacks remains lacking. In this study, behavioral response experiments were conducted with the aim of minimizing damage from group wasp attacks. The study species was Vespa velutina, which frequently causes wasp sting injuries in the southern regions of South Korea. Results demonstrated that worker wasps showed defensive behavior when a person approached within 3 m of the nest, and the attack rate was higher when the person conducted a large arm swing. When a person walked away after touching a nest, the number of workers attacking did not significantly decrease until they reached 5 m, this reduced to less than half when the person reached 10 m. Approximately 1.3 workers attacked even up to 300 m. However, when the person ran, the number of workers attacking was almost one or less after 10 m. Therefore, it is best to escape quickly to at least 10 m to reduce injury from group attacks. When wasps attacked, even if the person crouched, the attack did not decrease. Our recommended defensive behavior when wasps attack unexpectedly is that victims should turn their face in the opposite direction to the nest or the wasps, protect their face with their hands and arms, lean forward and run away rapidly to minimize injury. Wearing a wide brim hat was very effective, preventing about 75% of stings to the head, so this is also recommended.